WOMEN STRUGGLING WITH HYPERTENSION AND STRESS IN PREGNANCY AND THE ROLE OF PROLONGED USE OF NITRIC OXIDE SUPPLEMENTS: A META-ANALYSIS - Soomro, Khalida; Soomro, Muhammad Ali; Memon, Sadat (Journal of Pakistan Psychiatric Society, 2024)
Mental stress can contribute to the exacerbation of hypertension in pregnant women and preeclampsia by releasing stress hormones such as adrenaline and cortisol. Nitric oxide (NO) has an important role in stress, anxiety, and hypertension. OBJECTIVES To provide an understanding of the impact of nitric oxide, particularly the effects of L-arginine supplementation on mental stress and blood pressure regulation in pregnant women, to discuss the emerging concepts related to the pathogenesis of hypertension and preeclampsia, and also to highlight the potential benefits of L-Arginine and L-Citrulline supplementation in improving birth outcomes and maternal health. METHOD In this study, we focused on the role of L-arginine on high blood pressure during pregnancy. We did thorough research and effective communication of information from relevant and up-to-date research articles, studies from reputable sources, and great academic databases like PubMed, Google Scholar, and medical journals. Around 16 trials were searched in PubMed and Google Scholar. A total of six trials were included in this meta-analysis. RESULTS Nitric Oxide L-Arginine Supplementation showed a mean decrease in diastolic blood pressure and can lead to beneficial effects on blood pressure and vascular function, especially in pregnant mothers with stress, a mean increase up to 1.23 weeks (p = 0.002) for the gestation period to delivery, but did not show a reduction in systolic blood pressure as compared to placebo. CONCLUSION This meta-analysis study supports the notion that the availability of this substrate for NO synthesis prolongs the latency to the development of preeclampsia and decreases hypertension in a high-risk pregnant woman with hypertension and stress.